Single incision laparoscopic gastrostomy button insertion: A straightforward and efficient technique - Daniel VanZweden; Michael Leinwand (Journal of Pediatric Surgery Open)
Background: Gastrostomy button (G-button) placement is a common operation with multiple strategies for insertion: open, percutaneous endoscopic gastrostomy (PEG), standard laparoscopic, and single incision laparoscopic surgery (SILS). In 2016, we developed a SILS G-button procedure with several modifications which simplify the technique. We aim to demonstrate the feasibility of this new SILS G-button technique. Methods: SILS G-button operations performed from January 2016 to February 2024 were retrospectively evaluated. Age, gender, weight, operative time, duration of follow-up, and complications were recorded. Results: There were 71 patients in the cohort. The operation was faster in smaller children, with mean operative times of 23 min in children < 10 kg versus 36 min in children ≥ 10 kg (p = 0.002). Six patients (9 %) required an additional trocar. There were no major complications or conversions to an open procedure. Thirty-one patients (44 %) had granulation tissue. Two of these patients required operative excision. Conclusions: The SILS G-button technique is simple, effective, and completed in about 30 min. There is no wound except for the gastrostomy itself. The only complications were granulation tissue and dermatitis from leakage.